E-Konstituen: Inovasi Aplikasi Digital Berbasis Digital Operating System Untuk Meningkatkan Peran Generasi Muda di Era Demokrasi Digital - Alam Anugrah Ramadhan; I Putu Arya Aditia Utama; Jovialba Arkan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This study seeks to observe the importance of democracy in the digital era in realizing the Golden Indonesia 2045. The rapid development of technology and information has caused the world to enter the digital era so that all activities of human life begin to transition to the digital realm. Indonesia as one of the countries with large internet users has also transitioned into the digital era. All sectors of Indonesian people's lives have collaborated with digital media, although in some sectors, such as the political sector, especially in the democratic contestation, collaboration still needs to be improved. As a democratic country, the Indonesian people, especially the younger generation, need a wider space to be able to participate directly, but the space that should be created through digital media is still lacking to accommodate public participation, especially the younger generation in democracy. By using descriptive qualitative research methods and supported by primary and secondary data from questionnaires, books, journals, as well as various valid data from the internet, this study shows the need for digital applications to accommodate the community, especially the younger generation in democracy. Even though social media already exists, social media is still less effective and exclusive for carrying out democratic activities so that the participation of the younger generation and the contestation of democracy in the digital era is threatened to decline. Therefore, through the E-Constituent digital application, these problems can be overcome in order to realize Indonesia Gold 2045.